2022
DOI: 10.3390/jcm11185270
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Case-Control Study of Serum Metabolomics in Neonates with Late-Onset Sepsis and Necrotizing Enterocolitis

Abstract: Late-onset sepsis (LOS) and necrotizing enterocolitis (NEC) are major causes of neonatal morbidity and mortality. In this prospective, case-control study, we evaluated the metabolic profile of neonates with LOS and NEC. Blood samples were collected from 15 septic neonates and 17 neonates with NEC at the clinical suspicion of the specific diseases. Sixteen gestational and postnatal age-matched neonates without sepsis/NEC served as controls. Serum metabolic profiles were assessed using liquid chromatography–quad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Notably, the levels of PC and lysophosphatidylcholine (LPC), a derivative of PC, displayed corresponding changes. Conversely, reduced levels of PC and LPC were found in neonates with late-onset sepsis, accompanied by necrotizing enterocolitis [ 76 ]. PCs and LPC may also be considered prognostic markers for evaluating survival risk.…”
Section: Research Field Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the levels of PC and lysophosphatidylcholine (LPC), a derivative of PC, displayed corresponding changes. Conversely, reduced levels of PC and LPC were found in neonates with late-onset sepsis, accompanied by necrotizing enterocolitis [ 76 ]. PCs and LPC may also be considered prognostic markers for evaluating survival risk.…”
Section: Research Field Landscapementioning
confidence: 99%
“…Scientists explored the blood of preterm infants with both necrotizing enterocolitis and late-onset sepsis and found several distinguishing metabolites and proteins [ 181 ]. Another study showed that molecules identified as PCs or LPCs are both reduced in infants with late-onset sepsis, indicating their potential as biomarkers for early detection [ 76 ]. There is also a comprehensive study on changes in metabolites in neonates during a week of sepsis progression [ 182 ].…”
Section: Disease Study Landscapementioning
confidence: 99%
“…In 2022, Thomaidou et al [ 77 ] performed a case–control prospective study to investigate the blood metabolic profiles of NEC and LOS newborns. Blood samples from 15 septic newborns and 17 newborns with NEC were analyzed upon clinical suspicion of the specific pathology compared to those of 16 control newborns with corresponding gestational and postnatal ages without sepsis or NEC.…”
Section: Nec Metabolomics Biomarkersmentioning
confidence: 99%
“…Given the fact that the disease can develop in a sufficiently long period, both in the early and late neonatal period, predictive markers allow the identification of children at risk with a high probability of developing NECs, must be determined and have a high sensitivity and specificity in the first days of the child's life, until any traits of NEC are formed [9]. These indicators include markers of systemic immaturity, immaturity of the gastrointestinal tract and immune system, hypoxia, and no factors directly detecting the development of inflammatory reactions and/or damage to the intestine [11,12].…”
Section: Modern Systematics Neс With Etiopathogenesis Positionsmentioning
confidence: 99%
“…Functional immaturity of enzyme systems can be determined by direct determination of enzyme activity and/ or quantity [14], by detection of gene expression level [21], and indirectly by the level of metabolites being substrates/products of enzyme response [11,22,23].…”
Section: Modern Systematics Neс With Etiopathogenesis Positionsmentioning
confidence: 99%